Multi-user MC-CDMA using Walsh Code for Rayleigh and Gaussian Channel - Ghanim, M. F. (2011)
Multi-carrier code division multiple access (MCCDMA) systems receive a great deal of attention due to their great potential in achieving high data rates in wireless communication. This paper presents the simulation and analysis of MC-CDMA system performance when the data is sent and received over AWGN channel and Rayleigh channel. These two cases are simulated separately to show the performance of the MC-CDMA system when it has users, 4, 16, 32 and 64. For each SNR between 0dB and 50dB the BER value showed an effect of AWGN and Rayleigh fading channel on the MC-CDMA system.